Opportunistic adolescent health assessment in the child protection unit. (June 2016) - Hawkrigg, Sharon; Smith, LeAnne; Johnson, Alice; Kennedy, Andrew; Payne, Donald
Abstract : Aim: Adolescent health assessments are recommended to identify health‐risk behaviours. Adolescents who experience maltreatment are more likely to engage in such behaviours. This study (i) describes the frequency of health‐risk behaviours amongst adolescents attending a hospital‐based child protection unit (CPU) and (ii) determines whether use of a health assessment questionnaire increases the identification of these behaviours. Methods: A retrospective audit was performed of case notes of adolescents (aged ≥ 12 years) presenting to the CPU over 5 years (2007–2011). Data regarding health‐risk behaviours were extracted. In 2012, following the introduction of a standardised HEADSS‐based four‐page questionnaire, health‐risk data were collected prospectively over 18 months. The proportion of subjects reporting health‐risk behaviours, before and after questionnaire introduction, was analysed. Results: Two hundred fifty‐eight subjects, median age 13 (range 12–18) years, 78% female, were included in the pre‐questionnaire period; and 85 subjects, median age 14 (range 12–17) years, 86% female, were included following introduction of the questionnaire. Questionnaire use was associated with an increase in the frequency of health‐risk behaviours identified in the following domains: Education (odds ratio 4.48 [confidence interval 2.56–7.96] P < 0.001), Activities (16.18 [6.70–42.74] P < 0.001), Drugs/alcohol (4.00 [2.23–7.16] P < 0.001) and Suicidality (8.27 [4.59–14.92] P < 0.001). Participants reported higher rates of health‐risk behaviours than the national population. Conclusion: Adolescents attending a hospital‐based CPU report high rates of health‐risk behaviours. A standardised questionnaire results in increased identification of such behaviours.